Carcinoid Heart Disease: A Rare Complication of Metastatic Neuroendocrine Tumor - Afzal Qasim, Masroor Hussain Sharfi, Riffat Tanveer, Qasim Rauf, Muhammad Kashif Iltaf, Atif Ahmed Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Carcinoid heart disease (CHD) is a rare but severe complication of metastatic neuroendocrine tumors (NETs), primarily affecting the right-sided heart valves due to prolonged exposure to vasoactive substances such as serotonin. Objective: This study aims to evaluate the clinical, biochemical, and echocardiographic characteristics of CHD, as well as treatment outcomes and survival rates. Methods: This retrospective study was a multicenter study conducted during 2018 to 2023. A total of 25 patients were added to the study. Demographic and clinical data were collected, including the age, gender, and medical history of each patient. The primary symptoms observed included dyspnea, peripheral edema, fatigue, ascites, and signs of right-sided heart failure. Results: The study included 25 patients diagnosed with carcinoid heart disease, with a mean age of 52.3 ± 10.8 years. The gender distribution was 14 males (56%) and 11 females (44%). The most common clinical symptoms were dyspnea on exertion (76%), peripheral edema (64%), and fatigue (52%), indicative of right-sided heart failure. A strong positive correlation was observed between 5-HIAA levels and tricuspid regurgitation severity (r = 0.72, p < 0.01), indicating that higher serotonin levels contribute to worsening valvular fibrosis and dysfunction. Conclusion: Carcinoid heart disease is a progressive condition strongly associated with elevated biochemical markers and worsening valvular dysfunction over time. Regular echocardiographic monitoring and biomarker assessment are essential for early diagnosis and disease tracking. Keywords: Carcinoid heart disease, valvular dysfunction, 5-HIAA, NT-proBNP, somatostatin therapy, valve replacement